`Vineyard sprayer's lung': a new occupational disease. Issue 6 (November 1969) - Pimentel, J. Cortez; Marques, Fernando
Abstract : The mildew of the vineyards is prevented by the use of sprays with a solution of copper sulphate neutralized with hydrated lime. The inhalation of this solution while spraying may give rise to predominantly interstitial pulmonary lesions which may lead to respiratory insufficiency. These lesions, which were experimentally reproduced in guinea-pigs, have a well-defined histological picture characterized by three stages—intra-alveolar desquamation of macrophages, formation of predominantly histiocytic granulomas in the septa, and the healing of these lesions generally under the form of fibro-hyaline nodules very similar to those found in silicosis. These lesions contain variable amounts of copper. The pathogenesis of these lesions and the possibility of their regression when the offending agent is removed are discussed; and the value of lung biopsy and the necessity of protecting these workers are stressed.